Diseño del módulo de completamientos múltiples del manual general de completamiento de pozos de Ecopetrol S.A. (2017)
The design of the module developed in this project has been made in 3 phases. The first phase was the analysis of historical information to identify the wells with the multiple completions installed in the basins where Ecopetrol S.A has maintained its operations from 2005 to 2015. Following the above and in order to achieve the development of Phase 2, construction of a map of occurrences of multiple completions to identify, trends and candidate areas to install this type of completions. Finally, phase 3 involves the development of a theoretical matrix that allows the selection and identification of Wells proposed for a multiple completion through the identification of different variables such as permeability differences, user requirements and conditions that allow the installation of a multiple completion; as a final result the matrix will provide one or more recommendations as specified into it.